RESPONSE RATE OF PAKISTANI CHILDREN WITH ACUTE LYMPHOBLASTIC LEUKAEMIA TO MEDICAL RESEARCH COUNCIL ACUTE LYMPHOBLASTIC LEUKAEMIA 97 CHEMOTHERAPY PROTOCOL - Idris, Muhammad; Farid, Jamila; Sarwar, Javed; Ahmed, Suhaib; Wiqar, Muhammad Amin; Badsha, Shahida (Journal of Ayub Medical College Abbottabad, 2010)
Background: Acute lymphoblastic leukaemia (ALL), a malignancy of lymphoid lineage cells, has excellent prognosis in children. In Pakistan, a few studies highlighted the response of ALL to chemotherapy. The Present study was planned to see the response rate of Pakistani children with ALL to Medical Research Council ALL 97 (MRCALL97) chemotherapy protocol. This descriptive case series was conducted at the Department of Haematology, Armed Forces Institute of Pathology and the Department of Paediatric Oncology, Combined Military Hospital, Rawalpindi from 16th of February 2007 to 16th of August 2007. Methods: Diagnosed children with ALL fulfilling the inclusion criteria were interviewed regarding history of the present, past illnesses, and family history. Physical examination was performed. Presenting clinical features, blood counts and blood and bone marrow blasts percentage were used to see the response on day 29 post chemotherapy. The data was recorded on a structured proforma for statistical analysis. Results: A total of 33 patients were studied including 26 males and 7 females. Twenty-five patients belonged to age group 2-9 years, and 8 to <2 or >9 years, median age being 4.5 years. Presenting WBC count was <50Ã—109/L in 30 patients and >50Ã—109/L in 3 patients. At the end of induction, complete remission was achieved in 31 out of 33 (94%) patients while two patients did not achieve remission. Conclusion: Response rate of Pakistani children with ALL to chemotherapy was superior to the previously reported figures from Pakistan. Keywords: Acute Lymphoblastic Leukaemia, ALL, remission, chemotherapy